2017
DOI: 10.1056/nejmoa1608862
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Recombinant Influenza Vaccine in Adults 50 Years of Age or Older

Abstract: RIV4 provided better protection than standard-dose IIV4 against confirmed influenza-like illness among older adults. (Funded by Protein Sciences; ClinicalTrials.gov number, NCT02285998 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 24 publications
3
183
1
1
Order By: Relevance
“…Compared with standard‐dose influenza vaccine, high‐dose vaccine was also found to reduce hospital admission with respiratory illness and to be cost‐saving . Finally, a recombinant influenza vaccine has been shown to provide a better protection in older adults than the standard quadrivalent, inactivated influenza vaccine . At present, the availability of these newer vaccine products is limited in many settings, and where available, they may be cost‐prohibitive.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Compared with standard‐dose influenza vaccine, high‐dose vaccine was also found to reduce hospital admission with respiratory illness and to be cost‐saving . Finally, a recombinant influenza vaccine has been shown to provide a better protection in older adults than the standard quadrivalent, inactivated influenza vaccine . At present, the availability of these newer vaccine products is limited in many settings, and where available, they may be cost‐prohibitive.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Because the response to influenza M1 and NP, correlates with protection in both CD4 [68] and CD8 T cells [69], these internal proteins will be a necessary component of new vaccines for older adults. These internal proteins are absent in influenza subunit vaccines (HA +/− neuraminidase), so alternative mechanisms including antibody-mediated protection [106] may explain the enhanced protection of adjuvanted [57] and recombinant HA [107] formulations in older adults. A large randomized clinical trial of an AS03-adjuvanted influenza vaccine in older adults also showed enhanced protection against the influenza A/H3N2 vaccine strain compared to the unadjuvanted formulation [108], and this enhanced protection was comparable to that found in the randomized trial of high-dose influenza vaccine [109].…”
Section: The Role Of Influenza Internal Proteins and Adjuvants In Newmentioning
confidence: 99%
“…However, evidence for the effectiveness of these vaccines relative to those produced in eggs is 284 limited given that few head-to-head trials have been performed. One of these trials was carried out 285 during the 2014-2015 season with predominant circulation of antigenically drifted influenza A(H3N2), 286 and found 30% higher relative efficacy in older adults for a recombinant hemagglutinin-based vaccine 287 compared to standard egg-grown inactivated influenza vaccine [29]. Vaccines grown in eggs and in cell-288 culture were found to have similar efficacy overall in a placebo controlled trial carried out in [2007][2008]289 but only the cell-culture derived vaccine demonstrated statistically significant efficacy against influenza 290 A(H3N2) [30].…”
Section: Discussion 234mentioning
confidence: 99%